A laminopathic mutation disrupting lamin filament assembly causes disease-like phenotypes in Caenorhabditis elegans - Bank, Erin M. (The American Society for Cell Biology, 2011)
Mutations in the human LMNA gene underlie many laminopathic diseases, including Emery-Dreifuss muscular dystrophy (EDMD); however, a mechanistic link between the effect of mutations on lamin filament assembly and disease phenotypes has not been established. We studied the ΔK46 Caenorhabditis elegans lamin mutant, corresponding to EDMD-linked ΔK32 in human lamins A and C. Cryo-electron tomography of lamin ΔK46 filaments in vitro revealed alterations in the lateral assembly of dimeric head-to-tail polymers, which causes abnormal organization of tetrameric protofilaments. Green fluorescent protein (GFP):ΔK46 lamin expressed in C. elegans was found in nuclear aggregates in postembryonic stages along with LEM-2. GFP:ΔK46 also caused mislocalization of emerin away from the nuclear periphery, consistent with a decreased ability of purified emerin to associate with lamin ΔK46 filaments in vitro. GFP:ΔK46 animals had motility defects and muscle structure abnormalities. These results show that changes in lamin filament structure can translate into disease-like phenotypes via altering the localization of nuclear lamina proteins, and suggest a model for how the ΔK32 lamin mutation may cause EDMD in humans.